Financial and Non-Financial Feasibility Analysis Vaname Shrimp (Litopenaeus vannamei) with Different Technology in Purworejo, East Lampung - Qulubi, Muhammad Hadziq; Abidin, Zainal; Supono, Supono (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2023)
This research aims to analyze the financial and non-financial feasibility of vaname shrimp cultivation using three different cultivation technologies, namely simple, semi-intensive and intensive in Purworejo, Pasir Sakti Lampung, East Lampung. This research is a survey with a total of 13 respondents. The research results showed that the BEP volume for each technology was 151.94 kg, 4,825.55 kg and 5,755.12 kg. BEP prices for each technology are IDR38,491.07, IDR47,939.79 and IDR69,398.88. B/C ratio for each technology is 1.97, 2.49 and 2.39. The payback period for each technology is 2.29 years, 0.55 years and 0.66 years. The IRR for each technology is 69%, 58% and 50%. Thus, cultivating vaname shrimp using semi-intensive and intensive technology is very feasible to develop, while simple technology is quite feasible to develop. Sensitivity analysis of a 10% increase in feed prices has a sensitive impact on semi-intensive and intensive technology shrimp cultivation. The non-financial feasibility analysis of three cultivation technologies includes market, technical, technological, legal and socio-economic environmental aspects of implementation in accordance with the Regulation of the Minister of Maritime Affairs and Fisheries of the Republic of Indonesia Number 75/PERMEN-KP/2016 concerning General Guidelines for Raising Tiger Prawns and Vaname Shrimp, so that it can be declared worthy to continue.